Text, Speech and Dialogue 15th International Conference, TSD 2012, Brno, Czech Republic, September 3-7, 2012, Proceedings - Sojka, Petr; Horak, Aleš; Kopecek, Ivan; Pala, Karel (Lecture Notes in Artificial Intelligence,, 2012)
This book constitutes the refereed proceedings of the 15th International Conference on Text, Speech and Dialogue, TSD 2012, held in Brno, Czech Republic, in September 2012. The 82 papers presented together with 2 invited talks were carefully reviewed and selected from 173 submissions. The papers are organized in topical sections on corpora and language resources, speech recognition, tagging, classification and parsing of text and speech, speech and spoken language generation, semantic processing of text and speech, integrating applications of text and speech processing, machine translation, automatic dialogue systems, multimodal techniques and modeling.